Toxoplasma gondii tissue ... - Scherrer, Patrick; Ryser-Degiorgis, Marie-Pierre; Marti, Iris A.; St; Borel, ephanie; Frey, Caroline F.; Mueller, Norbert; Ruetten, Maja; Basso, Walter (Zenodo, 2023)
4.4. Occurrence of T. gondii tissue stages Tissue stages were rarely found in this study. Tissue cyst abundance in felids is indeed known to be low. At the FIWI, lynx organs are systematically screened by histology for general health evaluation (Ryser-Degiorgis et al., 2021) but tissue cysts of any kind were rarely observed (FIWI, unpublished data). Re-evaluation of selected cases in this study revealed a higher detection of protozoan tissue stages than initially recorded in routine diagnostics. Tissue cysts are small in early stages of infection and therefore easily missed. While mature T. gondii and Sarcocystis tissue cysts and Hepatozoon schizonts are easily identifiable in histological sections, early stages of these parasites might be occasionally misidentified, which makes diagnosis solely based on morphological criteria challenging. PCR techniques represent an adequate aid for parasite identification in histological sections. However, it has a low sensitivity, as parasite stages may be not present in ... : Published as part of Scherrer, Patrick, Ryser-Degiorgis, Marie-Pierre, Marti, Iris A., St, Borel, ephanie, Frey, Caroline F., Mueller, Norbert, Ruetten, Maja & Basso, Walter, 2023, Exploring the epidemiological role of the Eurasian lynx (Lynx lynx) in the life cycle of Toxoplasma gondii, pp. 1-10 in International Journal for Parasitology: Parasites and Wildlife 21 on pages 7-8, DOI: 10.1016/j.ijppaw.2023.03.005, http://zenodo.org/record/10668262 ...